Flagging the "new" South Africa, 1910-2010 (Historia, 2021)
Over the past century, distinctive flags have been devised for and adopted by South Africa on three occasions. These were progressive steps and in each instance the flags addressed both a current need in the constitutional development of South Africa, and marked a key milestone in the country’s flag history. The first of these came soon after Union in 1910 and followed a standard pattern applied throughout the British Empire. The second saw the hoisting in 1928 of a distinctive national flag, in recognition of South Africa’s independent status. At this time there were a few independent states in Africa, but within three decades, on a rising tide of African nationalism, this situation began changing. In sub-Saharan Africa, Ghana set the ball rolling in 1957, followed by Guinea a year later. The floodgates opened in 1960, when an unprecedented eighteen African countries gained independence, each of them under a new national flag. It was also the year in which the British prime minister, Harold McMillan, delivered his “winds of change” address to the South African parliament on 3 February. Three decades later, almost to the day, President F.W. de Klerk announced at the opening of parliament that political detainees would be released, and hitherto banned political organisations would henceforth be free to participate in the search for an equitable dispensation for all South Africans. This setin motion the formal negotiation process in South Africa, which came to fruition four years later. Cornelius Castoriadis, director of studies at the Ecole des Hautes Etudes et Sciences Sociales in Paris, and a leading figure in contemporary thought, remarks that any new society will obviously wish to create a new institutional symbolism.In his book Nationalism and Modernism, Anthony Smith points out that new national flags, anthems and other emblems of state which come into being with the rise of nation states, are part and parcel of the traditions that are created during such a process
Keywords: flags; South Africa; constitutional development; history; union; 1910; British Empire; 1928; national flag; independent status; African nationalism; sub-Saharan Africa; Ghana; 1957; Guinea; Harold McMillan; “winds of change”; President F.W. de Klerk; Cornelius Castoriadis; Ecole des Hautes Etudes et Sciences Sociales; Paris; Nationalism and Modernism; Anthony Smith